Relationship between ENSO cycles and frost events within the Pampa humeda region - Muller, Gabriela Viviana (2000)
The objective of the present paper is to analyse the possible impact of ENSO events on the spatial and the temporal distribution of frost occurrences, within the central region of Argentina. Therefore, the minimum temperature series have been studied for 41 meteorological stations within the Pampa Húmeda region and, for a period of 30 years from 1961 to 1990, exploring possible relationships with El Niño (EN)/La Niña (LN) events and the changes in the Southern Oscillation. It can be concluded that part of the frost frequency variability within this region is explained by the ENSO cycle. Results indicate that, for at least 1 of the 2 years in which the EN event takes place, the mean number of frost occurrences drops below the climatological value. The low phase of the Southern Oscillation Index (SOI) also coincides with those years for which the number of frost events remained below the total annual mean in all cases, with the year 1965 as an exception. Conversely, during the high phase of the SOI, this number was above the total annual mean for four of the six classified cases. In the particular case of seasonal frost occurrence, it is related to the warm event development state, exhibiting a greater impact during the autumn and winter months, for which the cold event also seems to have influence. Copyright © 2000 Royal Meteorological Society